Beyond Consolation : Death, Sexuality, and the Changing Shapes of Elegy - Zeiger, Melissa F. (Melissa Fran), 1957- (Book collections on Project MUSE., 1997)
"Using as her starting point the story of Orpheus and Eurydice, Melissa F. Zeiger examines modern transformations of poetic elegy, particularly as they reflect historical changes in the politics of gender and sexuality. Although her focus is primarily on nineteenth- and twentieth-century poetry, the scope of her investigation is grand: from John Milton's "Lycidas" to very recently written AIDS and breast cancer elegies."--Jacket